Should asymptomatic patients with congenital lung malformations undergo surgery? A decision analysis. Issue 2 (26th October 2022) - Yang, Weili; Gao, Ya; Li, Peng; Eckman, Mark H.
Abstract: Background: Congenital lung malformations (CLMs) are being detected more frequently during pregnancy. There is controversy regarding the optimal treatment for an asymptomatic child with prenatally diagnosed CLMs. Due to the paucity of information from clinical trials, we developed decision analytic models to compare two treatment strategies for such patients—elective surgical resection versus expectant management. Methods: We built decision analytic models stratified by lesion size. We used data from English language literature identified through PubMed searches along with estimates from expert opinions of surgical colleagues. We analyzed results for two hypothetical asymptomatic 6‐month‐old children with CLMs; one has a large lesion occupying more than 50% of the involved lobe, while the other has a small lesion occupying less than 50% of the involved lobe. We used quality‐adjusted life years (QALYs) to measure effectiveness. Results: For an asymptomatic child with a small or large lesion, expectant management resulted in a small gain of 0.09 or 0.15 QALYs, respectively. Sensitivity analyses showed that surgical resection would be preferred if the probability of remaining asymptomatic was low. Conclusions: In contrast to current practice, expectant management may be a better alternative for asymptomatic children born with CLMs. More longitudinal studies are required to improve the accuracy of the model.